Transformational odyssey : finding your path to personal transformation and self-renewal - Barner, Robert (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2017)
The Transformational Odyssey was written to help those individuals who are facing difficult life transitions, and who are attempting to successfully navigate tough life decisions and engage in deep self-discovery. Unlike other self-help books that attempt to provide readers with homespun advice for addressing difficult life challenges, The Transformational Odyssey shows readers how to take charge of their self-growth and development. It does this by providing readers with several applied techniques for engaging in deep self-learning in a more profound and fundamentally life-changing way.The title, The Transformational Odyssey, reflects the book's integrative metaphor of transformational learning as a personal odyssey of self-discovery. The word "odyssey" connotes a long, and sometimes arduous and meandering journey. Although an odyssey may present the traveler with unexpected trials and challenges, in the end it may yield increased wisdom and knowledge. Building on this metaphor, The Transformational Odyssey introduces readers to eight passages that they will inevitably encounter during their own personal odysseys of self-discovery. Each of these passages involves a uniquely different learning challenge that, as it is successfully navigated, increases the reader's capacity for self-growth.The Transformational Odyssey is written in a conversational style, as if the author were sitting down next to the reader to share my forty-plus years of experience as a personal coach and life transition counselor. Since different people learn in different ways, this book incorporates a variety of different learning methods, including actual cases, exercises, suggested actions, famous quotes, and metaphors. For those readers to would like to dig deeper on a given topic, at the end of each chapter the author has included a separate section that introduces readers to related cutting-edge research in the field of human psychology. The topics included in these sections cover such areas as mindfulness, meditation, narratives, and future selves.
"Charlotte, NC, www.infoagepub.com."
Keywords: Self-actualization (Psychology); Change (Psychology); Decision making -- Psychological aspects.; Life change events.; Self-help -- Personal Growth -- General.; Self-help, personal development and practical advice.; elektronické knihy; electronic books